Detecting Biogenic Amines in Food and Drug Plants with HPLC: Medical and Nutritional Implications - Cao Boyang ,; Alexander V. Oleskin ,; Tatiana Vlasova, (Journal of Pharmacy and Nutrition Sciences, 2020)
Background: This work reports the results of the initial stage of the project aimed at detecting neuroactive substances in tropical plants that are widely used as food and/or drugs. Methods: The content of neuroactive biogenic amines, e.g, dopamine (DA), norepinephrine (NE), epinephrine (E), serotonin (5-HT), and others was determined using high-performance liquid chromatography (HPLC) with amperometric detection in leaf samples from Plumeria rubra L. cv. acutifolia, Syzigium jambos (L.) Alston, Buxus megistophylla (or Euonymus japonicas cv. aureoma), and Cinnamomum bodinieri Levl. Results: The total fraction of disintegrated leaves contained (sub)micromolar concentrations of DA, NE, and 5-HT. They lacked E and the catecholamine precursor 2,3-dihydrophenylalanine (DOPA). Conclusions: From the data obtained, it is evident that heretofore unexplored tropical plants used in drug preparations (P. rubra and S. jambos) and as desserts (S. jambos) and spices (C. bodinieri) contain physiologically active concentrations of neurochemicals. The neurochemicals are expected to produce a significant effect on the people who consume preparations and food additives made from the aforementioned plants. Moreover, such plant preparations can potentially be used as psychoactive drugs for the purpose of intentionally manipulating human behavior.